Platelet-rich plasma improves pain and function in knee osteoarthritis: a retrospective study - Sun, Yi-Ting; Xiang, Xiao-Na; Yang, Jie; Peng, Jia-Lei; He, Hong-Chen (Frontiers in Physiology, 2025)
IntroductionThis study aimed to evaluate the efficacy of platelet-rich plasma (PRP) in treating knee osteoarthritis (KOA) and the effects of baseline characteristics and PRP intervention parameters on treatment outcomes.MethodsOverall, 140 individuals diagnosed with KOA who received PRP injections and completed a 6-month follow-up period were enrolled in this retrospective analysis. Knee pain and functional outcomes were assessed using the Visual Analog Scale (VAS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Based on the Minimal Clinically Important Difference (MCID) in outcomes, the participants were divided into effective and ineffective groups. Using multivariable logistic regression to explore factors influencing treatment outcomes, we compared the effective and ineffective groups to identify predictors of response to PRP therapy.ResultsAt 6 months, the median (IQR) VAS score significantly decreased from 66.5 (27) to 24 (34) (95% CI = −38 to −30.5), p < 0.001), and WOMAC scores improved from 29 (22) to 12 (14) (95% CI = −16.5 to −12), p < 0.001). Five mild adverse events were reported. Multivariate analysis indicated that only the number of injections significantly influenced VAS outcomes (OR = 4.285, 95% CI: 1.586–11.578, p = 0.004). Regarding WOMAC, multivariate analysis revealed that body mass index (BMI) (OR = 0.867, 95% CI: 0.755–0.995, p = 0.042) and disease duration (OR = 0.905, 95% CI: 0.784–0.989, p = 0.045) significantly affected outcomes. Age, sex, Kellgren-Lawrence (KL) grade, number of PRP injections, and injection frequency did not significantly impact WOMAC scores.ConclusionPRP therapy is a safe and effective treatment option for KOA. In this 6-month follow-up investigation, we observed that the number of injections administered affected pain levels, while disease duration and BMI affected knee joint function. Insights from this study may facilitate patient selection and PRP treatment protocol optimization in clinical practice.